Driving a motor vehicle and psychogenic nonepileptic seizures: ILAE Report by the Task Force on Psychogenic Nonepileptic Seizures. Issue 3 (9th June 2020) - Asadi‐Pooya, Ali A.; Nicholson, Timothy R.; Pick, Susannah; Baslet, Gaston; Benbadis, Selim R.; Beghi, Massimiliano; Brigo, Francesco; Buchhalter, Jeffrey; D'Alessio, Luciana; Dworetzky, Barbara; Gigineishvili, David; Kanaan, Richard A.; et al.
Abstract: Objectives: This International League Against Epilepsy (ILAE) Report: (a) summarizes the literature about "driving and psychogenic nonepileptic seizures (PNES)"; (b) presents the views of international experts; and (c) proposes an approach to assessing the ability of persons with PNES (PwPNES) to drive. Methods: Phase 1: Systematic literature review. Phase 2: Collection of international expert opinion using SurveyMonkey®. Experts included the members of the ILAE PNES Task Force and individuals with relevant publications since 2000. Phase 3: Joint analysis of the findings and refinement of conclusions by all participants using email. As an ILAE Report, the resulting text was reviewed by the Psychiatry Commission, the ILAE Task Force on Driving Guidelines, and Executive Committee. Results: Eight studies identified by the systematic review process failed to provide a firm evidence base for PNES‐related driving regulations, but suggest that most health professionals think restrictions are appropriate. Twenty‐six experts responded to the survey. Most held the view that decisions about driving privileges should consider individual patient and PNES characteristics and take account of whether permits are sought for private or commercial driving. Most felt that those with active PNES should not be allowed to drive unless certain criteria were met and that PNES should be thought of as "active" if the last psychogenic seizure had occurred within 6 months. Significance: Recommendations on whether PwPNES can drive should be made at the individual patient level. Until future research has determined the risk of accidents in PwPNES a proposed algorithm may guide decisions about driving advice.